Cocaine-induced midline destruction. Issue 2 (15th February 2021) - Ide, Veerle; Henckaerts, Liesbet; Vanbrabant, Peter; Vanderschueren, Steven
ABSTRACT: In patients presenting with nasal septum perforation, the differential diagnosis between ANCA-associated vasculitis and cocaine-induced midline destruction (CIMD) can be challenging. We describe the case of a 28-year old man who presented with a nasal septum perforation. He admitted the use of cocaine and showed no other symptoms of systemic inflammation. Perinuclear anti-neutrophilic cytoplasmatic antibodies (p-ANCAs) came back positive, as did anti-proteinase 3-antibodies. Further testing revealed antibodies to human neutrophil elastase (HNE), typically found in CIMD but rarely in ANCA-associated vasculitis. The combination of an atypical ANCA-pattern and the detection of HNE-antibodies led to the diagnosis of CIMD. In conclusion, HNE antibodies can be used to distinguish between CIMD and ANCA-associated vasculitis.